School refusal in children and fear of future situations - Gonzálvez, Carolina; Martín , Miriam; Fernández-Sogorb, Aitana (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
During schooling, every individual may be deal with school situations that can cause fears. This study aims to examine the differences in school refusal based on the high and low scores in anticipatory anxiety and to analyze the predictive capacity of school refusal on anticipatory anxiety. A total of 879 Spanish students aged between 8 and 11 years old participated. Students with high Anticipatory Anxiety scores obtained higher mean scores in school refusal, and school refusal was a positive and statistically significant predictor of Anticipatory Anxiety in most cases. Findings for improving school attendance are discussed.